2020
DOI: 10.1101/2020.05.26.20105700
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitude, and practice regarding COVID-19 outbreak in Bangladeshi people: An online-based cross-sectional study

Abstract: In Bangladesh, an array of measures have been adopted to control the rapid spread of the COVID-19 epidemic. Such general population control measures could significantly influence perception, knowledge, attitudes, and practices (KAP) towards COVID-19. Here, we assessed KAP towards COVID-19 immediately after the lock-down measures were implemented and during the rapid rise period of the outbreak. Online-based cross-sectional study conducted from March 29 to April 19, 2020, involving Bangladeshi residents aged 12… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
68
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 25 publications
(30 reference statements)
17
68
9
Order By: Relevance
“…This study revealed that 56.4% of study participants had a positive attitude towards the prevention and control measures of COVID-19 pandemic. This finding is lower than studies conducted in eight teaching hospitals, Ethiopia (94.7%) [27], Indian medical students (93.7%) [31], Syrian residents (63.5%) [39], Malaysian residents (83.1%) [36], Bangladesh (62.3%) [24], Sudan (81.8%) [38], 10 universities in Shaanxi Province, China (73.8%) [49], Uganda (72.4%) [50], and India (97.3%) [51]. However, this result is higher than the studies conducted in Pakistan (44%) [28], and Makerere University Teaching Hospitals (21%) [25].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…This study revealed that 56.4% of study participants had a positive attitude towards the prevention and control measures of COVID-19 pandemic. This finding is lower than studies conducted in eight teaching hospitals, Ethiopia (94.7%) [27], Indian medical students (93.7%) [31], Syrian residents (63.5%) [39], Malaysian residents (83.1%) [36], Bangladesh (62.3%) [24], Sudan (81.8%) [38], 10 universities in Shaanxi Province, China (73.8%) [49], Uganda (72.4%) [50], and India (97.3%) [51]. However, this result is higher than the studies conducted in Pakistan (44%) [28], and Makerere University Teaching Hospitals (21%) [25].…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is lower than a study done in Syria (73.8%) [39], Pakistan (80.5%) [44], Sudan (89.9%) [38], students in 10 universities in Shaanxi Province, China (87.9%) [49], Uganda (85.3%) [50]. However, this finding is higher than studies conducted in Debre Birhan University Undergraduate students (49.5%) [34], Bangladesh (55.1%) [24], Pakistan (57.3%) [28]. The differences in the practice of preventive measures could have been subjected to variation in the cut-off values to classify good or poor practice.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Participants' knowledge, attitudes, and practices towards the COVID-19 were measured using a total of 28 items structured questions (including 17-item for knowledge, 7-item for attitudes, and 6-item for practices) based on the two prior studies (19,20) Table 2). The correct answer ('True') was coded as 1, while the wrong answer ('False') was coded as 0 (19).…”
Section: Knowledge Attitudes and Practices (Kap)mentioning
confidence: 99%